2022
DOI: 10.3390/molecules27061783
|View full text |Cite
|
Sign up to set email alerts
|

Significant Roles of Notch O-Glycosylation in Cancer

Abstract: Notch signaling, which was initially identified in Drosophila wing morphogenesis, plays pivotal roles in cell development and differentiation. Optimal Notch pathway activity is essential for normal development and dysregulation of Notch signaling leads to various human diseases, including many types of cancers. In hematopoietic cancers, such as T-cell acute lymphoblastic leukemia, Notch plays an oncogenic role, while in acute myeloid leukemia, it has a tumor-suppressive role. In solid tumors, such as hepatocel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 156 publications
(253 reference statements)
1
3
0
Order By: Relevance
“…As mentioned previously, alterations of glycosyltransferases associated with O- glycosylation of N1 have been reported in cancers ( 15 , 16 ). This is notably the case for POFUT1, where amplification, mutation, or upregulation has been found in hepatocellular carcinoma ( 35 ), colorectal cancer ( 36 , 37 ), glioblastoma ( 38 ), and squamous cell carcinoma ( 39 ).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…As mentioned previously, alterations of glycosyltransferases associated with O- glycosylation of N1 have been reported in cancers ( 15 , 16 ). This is notably the case for POFUT1, where amplification, mutation, or upregulation has been found in hepatocellular carcinoma ( 35 ), colorectal cancer ( 36 , 37 ), glioblastoma ( 38 ), and squamous cell carcinoma ( 39 ).…”
supporting
confidence: 54%
“…Conversely, a gain of function (GOF) of N1 has been found in various lymphomas/leukemia ( 11 , 12 , 13 ) and breast cancer ( 14 ). Glycosylation of the Notch extracellular domain (NECD) regulates its activity and is essential for its function, and alterations in the glycosyltransferases modifying the NECD have been implicated in a number of cancers ( 15 , 16 ).…”
mentioning
confidence: 99%
“…Consequently, UDP-GlcA decarboxylase purifies with NAD + stoichiometrically bound . The same is true for the reactions catalyzed by three other human homologs of ArnA_DH: UDP-glucose epimerase (GALE), central to the Leloir pathway of galactose metabolism, protein glycosylation, and the synthesis of proteoglycans and glycolipids; , GDP-mannose 4,6-dehydratase in the pathway for biosynthesis of the essential sugar donor GDP-fucose, whose deficiency leads to blood disorders and significantly impacts cancer biology; and dTDP-glucose 4,6-dehydratase with unknown function in humans but whose mutation-impairing activity causes the Catel–Manzke syndrome . These three enzymes catalyze NAD­(P) + -dependent oxidation of a sugar nucleotide 4′ hydroxyl but retain the resulting NAD­( P )H to catalyze a subsequent reductive step (SI Figure S7B–D).…”
Section: Discussionmentioning
confidence: 96%
“…Studies have indicated that O-GlcNAcylation may potentially ameliorate cancer, diabetes, and neurodegenerative diseases. 17 , 18 , 19 , 20 Moreover, PTMs play a role not only in regulating human diseases but also in plants. 21 , 22 , 23 , 24 Different PTMs that are related to each other and involved in dynamic transcriptional reprogramming play a role in fruit ripening.…”
Section: Introductionmentioning
confidence: 99%